The MYC Paralog-PARP1 Axis as a Potential Therapeutic Target in MYC Paralog-Activated Small Cell Lung Cancer - Bian, Xing; Wang, Xiaolin; Zhang, Qiuyan; Ma, Liying; Cao, Guozhen; Xu, Ao; Han, Jinhua; Huang, Jun; Lin, Wenchu (Frontiers in Oncology, 2020)
Poly (ADP-ribose) polymerase 1 (PARP1) is highly expressed in small cell lung cancer (SCLC) and has emerged as an attractive target for treatment of SCLC. However, the clinical significance of PARP1 expression in SCLC remains elusive. In this study, we showed that high PARP1 expression was associated with better overall survival (OS), and was positively correlated with the expression of MYC paralogs in patients with SCLC. We demonstrated that PARP1 was transcriptionally regulated by MYC paralogs. Integrative analysis of multiple RNA-seq data sets indicated that DNA damage response (DDR) genes involved in the replication stress response (RSR) and homologous recombination (HR) repair pathways were highly enriched in MYC paralog-addicted SCLC cell models and in human SCLC specimens. Targeting the MYC paralog-PARP1 axis with concomitant BET and PARP inhibition resulted in synergistic effects in MYC paralog-activated SCLC. Our study identified a critical PARP1 regulatory pathway, and provided evidence for a rational combination treatment strategy for MYC paralog-activated SCLC.